2023
DOI: 10.1002/adma.202204938
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategies for Hydroxyapatite‐Based Materials to Enhance Their Catalytic Performance and Applicability

Abstract: Hydroxyapatite (HAP) is a green catalyst that has a wide range of applications in catalysis due to its high flexibility and multifunctionality. These properties allow HAP to accommodate a large number of catalyst modifications that can selectively improve the catalytic performance in target reactions. To date, many studies have been conducted to elucidate the effect of HAP modification on the catalytic activities for various reactions. However, systematic design strategies for HAP catalysts are not established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 283 publications
0
12
0
Order By: Relevance
“…Thus, the synthesis and ripening media significantly influence the morphology and textural properties of HA powders. As the interest in HA as a promising catalyst for a variety of catalytic reactions has increased exponentially over the past 3 decades [ 78 ], the modification of its mesoporous structure could provide significant benefits in the green chemistry industry, making it a worthy competitor to silica and alumina catalysts [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the synthesis and ripening media significantly influence the morphology and textural properties of HA powders. As the interest in HA as a promising catalyst for a variety of catalytic reactions has increased exponentially over the past 3 decades [ 78 ], the modification of its mesoporous structure could provide significant benefits in the green chemistry industry, making it a worthy competitor to silica and alumina catalysts [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a slight shift and weakening of Ca and P peaks in HAp-Zn compared to HAp. HAp has excellent metal ion adsorption properties [6,36], and its adsorption mechanisms include (i) a dissolution-precipitation mechanism, which means that HAp first dissolves phosphate and then combines with metal ions; and (ii) an adsorption-replacement mechanism, whereby metal ions are first adsorbed on the surface of hydroxyapatite and then replace Ca 2+ . Based on the above results, it is suggested that HAp-Zn predominantly involved an adsorption-replacement mechanism, further facilitating the heteronucleation of ZIF-8 crystals on the surface of HAp.…”
Section: Binding Interactions Between Zif-8 and Hapmentioning
confidence: 99%
“…Titanium (Ti) and its alloys have found extensive applications as metallic bone implants [1], attributed to their remarkable mechanical properties and biocompatibility [2][3][4]. In order to enhance the fixation of Ti-based implants to bone, hydroxyapatite (HAp) coatings are fabricated on the implant surfaces in clinical settings as HAp constitutes the inorganic composition of natural bone [5][6][7][8]. Although HAp-coated implants have achieved successful applications in the past several decades, implant-associated infections (IAIs) which result from bacterial adhesion and biofilm formation seriously impair clinical outcomes of implants [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, unlike conventional inorganic bone repair materials such as HAp, P(VDF‐TrFE) seems unable to supply sufficient mineral ions (Ca 2+ and PO 4 3− ) which are necessary for bone formation. [ 151 ] Therefore, BG particles, which possesses superior biocompatibility, osteoconductive, and osteoinductive abilities, were introduced into P(VDF‐TrFE) to form P(VDF‐TrFE)‐BGM scaffolds. These bioactive multifunctional scaffolds remarkably improved the proliferation, adhesion, and osteogenesis differentiation of BMSCs, and significantly enhanced the formation of periosteum‐like tissue and the bone regeneration at the center of bone defect.…”
Section: Impact Of Electric Signalsmentioning
confidence: 99%